As repercussões da aplicação do incidente de desconsideração da personalidade jurídica no juizado especial cível - Lazzaretti, Levington de Oliveira (2019)
The present dissertation is inserted in the Research Line of Constitutional Jurisdiction and Democracy. The objective it is to study the repercussions of the application of the procedure of the Incident of Disregard of Legal Personality provided for in the Code of Civil Procedure of 2015 in the Small Claims Court. For that, the evolution and the foundations of the Special Civil Courts in the Brazilian legal system and the ways of approaching the citizen to the Judiciary Power were analyzed. We also studied the formation and development of legal personality of legal entities, and then we verified the evolution of the theory of disregard of legal personality until its prediction in Brazilian legislation. The hypothesis of applying the disregard provided for in the Consumer Defense Code and the Civil Code was worked out. In addition, the procedure for disregarding provided for in the Code of Civil Procedure was investigated, as well as the repercussions of the application of this rule in the Special State Civil Court, given the peculiarities of this special system in relation to the common procedure. Finally, we examined the problems presented by some professors of the application of the Incident of Disregard of Legal Personality in the scope of the Special Civil Court, as well as, in the end, a suggestion of solution presented by the doctrinaires and jurisprudence was presented. Key-words: Effective Access to Justice. Incident of Disregard